Surfing the Internet-of-Things: Lightweight Access and Control ofWireless Sensor Networks Using Industrial Low Power Protocols - Zhengguo Sheng; Chunsheng Zhu; Victor C. M. Leung (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2014)
Internet-of-Things (IoT) is emerging to play an important role in the continued advancement of information and communication technologies. To accelerate industrial application developments, the use of web services for networking applications is seen as important in IoT communications. In this paper, we present a RESTful web service architecture for energy-constrained wireless sensor networks (WSNs) to enable remote data collection from sensor devices in WSN nodes. Specifically, we consider both IPv6 protocol support in WSN nodes as well as an integrated gateway solution to allow any Internet clients to access these nodes.We describe the implementation of a prototype system, which demonstrates the proposed RESTful approach to collect sensing data from a WSN. A performance evaluation is presented to illustrate the simplicity and efficiency of our proposed scheme.